Comparative assessment of user-satisfaction with on-campus residential accommodation at Takoradi Technical University, Ghana - Osei - Poku, Gloria; Braimah, Anita; Clegg, Rebecca (Penerbit Universiti Kebangsaan Malaysia, 2020)
The satisfaction levels of residents in two types of on-campus accommodation at Takoradi Technical University were measured and compared in this study. Attributes used to assess the levels of satisfaction were grouped under physical features, social amenities and management factors. Using a cross-sectional research design, the study utilised a structured questionnaire to obtain the views of residents in one purpose-built hostel and three halls of residence that were converted from dormitory blocks. Cluster sampling was employed to group the population according to their respective halls while a total sample of 650 students were selected by the simple random sampling method out of 1,020 residents in the 2017/ 2018 academic year. Data analysis was done with SPSS v 21 and presented as frequency tabulation, mean score rankings and Relative Satisfaction Index (RSI). The results revealed a disparity in the satisfaction levels with residents in the purpose-built hall showing a higher value (54.8 %) than their counterparts in the converted halls (44.6 %). Although the overall scores for both halls indicate a neutral stance, the individual RSI values evince that students in the purpose-built hall are more satisfied with their accommodation. Some recommendations for the improvement of residential satisfaction in the existing halls of residence include the provision of internet access (Wi-Fi) and improved water supply. The study further suggested that new halls should be built; incorporating barrier-free systems to make them accessible for all manner of persons.